Clomazone Retention in Agricultural Soil - Cuadra, Pablo Nicolas (2023)
Clomazone (CLM), is an herbicide from the oxazolidinone chemical group (Carotenoid synthesis inhibitors), is a selective pre- and post-emergence herbicide indicated for application in rice. It is absorbed both by the roots and by the aerial growth points of weeds and therefore can be applied both pre- and post-emergence. Once in the soil, the adsorption-desorption process are the main mechanism that will determine its passage into the groundwater. The objective of this work is to study the adsorption and desorption of CLM in an agricultural soil for vegetable cultivation, carrying out batch type experiments. The results obtained indicate that the adsorption capacity of the soil is high, decreasing with temperature indicating that the process is exothermic. On the other hand, the desorption process is irreversible, reducing the lixiviation and contamination capacity of underground layers.